Dietary Betaine Addition Alters Carcass Traits, Meat Quality, and Nitrogen Metabolism of Bama Mini-Pigs - Cheng, Yating; Song, Mingtong; Zhu, Qian; Azad, Md. Abul Kalam; Gao, Qiankun; Kong, Xiangfeng (Frontiers in Nutrition, 2021)
Betaine is widely used as feed additives in animal husbandry as it can cause many benefits such as improving antioxidant ability, growth performance, and carcass traits. However, there are limited studies about the effects of betaine on the Bama mini-pigs. The present study was conducted to evaluate the effects of dietary betaine on carcass traits, meat quality, and nitrogen metabolism of pigs. Twenty-six pregnant Bama mini-pigs and then 104 weaned piglets were assigned for experimental treatments. The plasma and muscle samples were collected at 65-, 95-, and 125-d-old pigs, respectively. The results showed that betaine addition in the sow-offspring diets increased the lean meat rate in the 65-d-old pigs, whereas carcass weight, carcass yield, and loin-eye area were increased in the 95-d-old pigs, and carcass weight and backfat thickness in the 125-d-old pigs. Dietary betaine addition in the sow-offspring diets increased the contents of plasma Asp of 65-d-old, Met of 95- and 125-d-old, and Sar of 125-d-old pigs. Moreover, betaine addition increased the contents of Met, His, Ile, and Phe in Longissimus thoracis et lumborum, whereas those contents were decreased in biceps femoris and psoas major muscles at different stages. Betaine addition in the sow and piglets' diets regulated the muscle fiber-type and myogenic regulatory gene expressions. In summary, betaine addition in the sow and sow-offspring diets could improve the carcass traits and meat quality by altering the plasma biochemical parameters, amino acid composition, and gene expressions of skeletal muscle.